Qardhul Hasan Sebagai Pembiayaan Sosial Dalam Mengatasi Kemiskinan - Fauzi, Muchamad Rizky; Alfarda, Wahidatun Nafiah; Supriyanto, Supriyanto (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
Qardhul Hasan as Social Financing in Combating Poverty. The well-being of the people is the primary objective of the establishment of a nation. However, for developing countries, it is still a homework in tackling poverty. The Islamic Shariah manages poverty primarily to reduce poverty with funds derived from zakat, infaq, and sedekah. Indonesia, as the country with the largest number of Islamic believers in the world, has the potential to have large funds for zakat, infaq, and sedekah, but the current management is still not at its maximum. This research is aimed at exploring the literature on financing Qardhul Hasan as a means of combating poverty. Among them is an increase in profits of up to six times. Besides, there are other advantages, such as improved customer skills. With increased sharia financial inclusion, financing for the community can improve the well-being of the community and reduce the poverty rate.